Pendapatan dan Kelayakan Usahatani Kacang Tanah (Arachis Hypogaea L) di Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Fauzi, Dian; Dermawan, Alvindo; Supriadi, Dedi (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2024)
Peanuts are an agricultural commodity with high economic value and are a source of protein in Indonesian food. This research aims to analyze the income and feasibility of peanut farming in Batang Kapas District. The respondents used were 43 farmers. The analytical tools used are revenue and profit analysis, R/C, B/C, production BEP, price BEP, and revenue BEP. The results of the research show that the income of peanut farmers in Batang Kapas District is IDR 4,341,064.88 while the profit is IDR 2,694,404.41, R/C 1.32, so peanut farming in Batang Kapas District is profitable, then B/C is 0.32. The production BEP is 351.18 Kg and the price BEP is IDR 9,089.68 Kg, while the revenue BEP is IDR 4,222,206.33 per MT. In order for income and profits from peanut farming in Batang Kapas District to increase, it is hoped that farmers can improve the method of cultivating peanuts. It is hoped that Peanut farmers in Batang Kapas District can increase their farming production.